Guinea : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
The statistical data on gross domestic product, consumer price index, financial operations of the central government, central government revenue and expenditure of Guinea are presented in this paper. The data on monetary survey, summary accounts of the central bank, summary accounts of deposit money banks, sectoral distribution of credit, quarterly distribution of credit by sector and maturity, balance of payments, composition of merchandise exports, debt-service liabilities on external public debt, nominal exchange rate and effective exchange rates indices, and related economic indices are also presented.